Alternating ring-opening copolymerization of epoxides with saturated and unsaturated cyclic anhydrides: reduced viscosity poly(propylene fumarate) oligomers for use in cDLP 3D printing. Issue 19 (28th April 2020) - Shin, Yongjun; Becker, Matthew L.
Abstract : A ring-opening copolymerization of propylene oxide with saturated and unsaturated anhydrides using Mg(BHT)2 (THF)2 catalyst followed by an isomerization yields poly(propylene fumarate) (PPF) oligomers with improved properties for 3D printing. Abstract : A ring-opening copolymerization of propylene oxide with saturated and unsaturated anhydrides using Mg(BHT)2 (THF)2 catalyst followed by an isomerization yields poly(propylene fumarate) (PPF) oligomers with well-defined molecular mass, narrow molecular mass distribution, quantitative end-group fidelity, and a reduced viscosity compared to PPF. Mass spectrometry analyses and kinetic studies show that the resulting copolymers have gradient compositional sequencing. The lower viscosity of the statistical copolymer affords 3D printing with a lower diluent fraction (30 wt%) and higher molecular mass copolymer in the resin formulations. We also show that the mechanical properties of the printed structures can be tailored according to the monomer composition and resin formulation.